Enhancing translation teaching for L2 learners through ChatGPT: A study of AI-assisted Arabic-German translation - Naqrash, Nadia; Jarrah, Marwan; Hasan , Esraa; Ali , Sukayna (East European Journal of Psycholinguistics, 2025)
This study investigates the effectiveness of using ChatGPT as a teaching tool in enhancing Arabic-to-German translation skills. An experimental group, using ChatGPT throughout a 15-week semester, was compared to a control group that followed traditional translation instruction methods. Pre- and post-tests were administered to assess translation performance. Results demonstrated that students in the experimental group significantly outperformed those in the control group, showing improvements in sentence structure, vocabulary selection, grammatical accuracy, and the translation of idioms and collocations. Despite minor linguistic errors, students using ChatGPT showed greater progress in understanding translation nuances. The study highlights the potential of AI-powered tools in language learning, particularly in translation pedagogy, and suggests future research directions, including the long-term impact of AI on advanced translation skills, and the balance between machine and human input in the educational process. This study contributes to the growing body of literature on AI-assisted language teaching. Acknowledgements The study is funded in the framework of the project titled "Using ChatGPT in translation", University of Jordan, reg. No. 00104365. Disclosure Statement The authors reported no potential conflicts of interest.